CONTAMINATION OF ESCHERICHIA COLI IN ES CAMPUR SOLD AT PETISAH MARKET IN MEDAN CITY - Debie Rizqoh; Oktavia Silalahi (Proceeding B-ICON, 2023)
Es Campur is a typical Indonesian drink that is made by mixing various types of drink ingredients in sweet syrup. Es Campur can be contaminated with Escherichia coli bacteria through unsterilized tools. This study aimed to determine the presence of E. coli in Es Campur being traded around the Petisah Market in Medan. Data analysis was carried out descriptively by looking at the percentage in the form of frequency and then analyzed by comparing the existing literature theory. The study used Lactose Broth, Endo Agar, IMVIC and TSI media. The population in this study were all Es Campur, traded around the Medan Petisah Market. Es Campur is contaminated with E. coli. The results of the Es Campur research conducted from 10 samples were two samples contaminated with E. coli bacteria. It is suggested to the public that when buying Es Campur, they need to pay attention to the cleanliness of the places where they are sold, whether it is the place used to wrap Es Campur drinks.